Chapter 40: Sweetpotato Production in Florida - Eric H. Simonne; Stephen M. Olson; Mary L. Lamberts; William M. Stall; Kenneth L. Pernezny; Susan E. Webb (EDIS, 2019)
This document is HS738, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.